If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 5y = 2forx Solving 6x + 5y = 2forx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2forx' to each side of the equation. 6x + -2forx + 5y = 2forx + -2forx Reorder the terms: -2forx + 6x + 5y = 2forx + -2forx Combine like terms: 2forx + -2forx = 0 -2forx + 6x + 5y = 0 Add '-5y' to each side of the equation. -2forx + 6x + 5y + -5y = 0 + -5y Combine like terms: 5y + -5y = 0 -2forx + 6x + 0 = 0 + -5y -2forx + 6x = 0 + -5y Remove the zero: -2forx + 6x = -5y Combine like terms: -5y + 5y = 0 -2forx + 6x + 5y = 0 The solution to this equation could not be determined.
| 9x+2=4x-3 | | x=10+1.5y | | -4(2x-3)=2(x+4) | | 12v^2+29v+15= | | 2(x-1)=9x-37 | | 3(2x-8)=5(2x+8) | | -14-2k=-8-5(-8+5k) | | 16=8+(-a) | | 0.15y+0.08(y+4000)=1240 | | f(x)=2.45x^2-6.13x-3.68 | | 6-5(2x+3)=11 | | 2(x+4)+7x=3(x+4) | | 6(x-3)+2x-5=27 | | 2x+4+3(2x+2)=34 | | h=2.5433(7.5)+28.465 | | 4x+3x+9=2(x+8) | | 9x+2=7x+3x-5 | | 2m-3-3m=20-m | | 8M-4M-6-3+5M=56-1 | | 2x^3-18x=2x(x-3)(x+3) | | 5x+9+2x+7=2x+11 | | 7.5=3.2-2.1 | | -28+s=11 | | 6+2(x+4)=3(x+5) | | 1.5x-3.5=-.5 | | 2/3x-7/2=-1/2 | | 3/2x7/2=-1/2 | | 15=-5+zx-18 | | 37=.0021x^2-.286x+16.28 | | 3x+2y-z=9 | | 9=(x-41)/18 | | X+5+(-5)=11 |